A Study of Customers Perception and Satisfaction towards New Payment Technology - Priyanka, Dr. Pragati Saxena and Prof. (Dr.) Dinesh Chand (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
New payment technologies are bolstered India’s digital infrastructure known as India stack, a unified software platform aimed at presence-less, paperless, and cashless service delivery for their customers. Nowadays banks are going to provide smart services to satisfy the customers. There are various heterogeneous elements arousing the consumers to use the digital payment such as a rise in disposable income, the introduction of new products and services & expansion of entertainment sector. But there are also some elements which are the reasons for the low rate of acceptance of digital payment like, fees on digital platforms, perceive lack of customers’ desire to pay digitally, piracy of personal data & increase the burden of the tax liabilities. New payment technologies aim to compete by providing intuitive, simple, and efficient applications that prioritize customer experience. This study also based on, to know the customers perception and satisfaction towards new payment technologies.